FRI0136 Persistence of monotherapy or combination therapy with disease-modifying agents in patients with psoriatic arthritis in a real-world setting. (12th June 2018) - Mease, P.J.; Accortt, N.A.; Rebello, S.; Etzel, C.; Harrison, R.W.; Aras, G.A.; Gharaibeh, M.M.F.; Greenberg, J.D.; Collier, D.H.
Abstract : Background: Until recently, treatment for moderate to severe psoriatic arthritis (PsA) mainly focused on conventional synthetic disease-modifying antirheumatic drugs (csDMARDs) and tumour necrosis factor inhibitors (TNFis). However, the persistence of TNFis alone or in combination with csDMARDs is not well understood. Objectives: To assess real-word treatment patterns among patients with PsA receiving TNFi monotherapy, csDMARD monotherapy, or TNFi and csDMARD combination therapy. Methods: This retrospective study utilised data from patients with PsA aged ≥18 years, enrolled in the Corrona PsA registry between March 21, 2013, and July 31, 2017, treated with a TNFi and/or csDMARD (index therapy), and with ≥6 months of follow-up time. Patients were stratified by prevalent (initiation before enrollment) or incident (initiation after enrollment) therapy use; cohorts were based on index therapy: TNFi monotherapy, csDMARD monotherapy, or combination therapy. Outcomes of interest were the percentage of patients who were persistent on their index therapy or had a therapy change (discontinued, switched, or restarted) 12 months after the index visit. Results: There were 1266 patients in this study: 1144 prevalent and 122 incident (table 1). Patient characteristics at the index date were similar among patients; however, csDMARD monotherapy patients had higher disease activity than either TNFi group. Among prevalent patients, TNFi monotherapy patients were likely to be female (59%) and younger (51.9 years), nearly all patients had psoriasis, and BSA was similar and ≤5. At month 12, among patients with a follow-up visit within the 9–15–month window, the vast majority of prevalent patients and half of incident patients were persistent on their index therapy, and one quarter to one third of incident patients discontinued or switched therapy (table 1). Conclusions: Most patients who were prevalent on therapy at the time of enrollment in Corrona remained persistent on their therapy for 12 months in this study, while roughly half of patients initiating therapy after enrollment remained persistent over the same period. Young, female patients were more likely to receive TNFi monotherapy; the TNFi monotherapy cohort was associated with the least disease activity. The incident group was not different from the prevalent group. Although the prevalent group is more likely to have patients who responded to treatment, the data suggest that most therapy changes occur within the first year of PsA treatment. Disclosure of Interest: P. Mease Grant/research support from: AbbVie, Amgen, Bristol Myers Squibb, Celgene, Janssen, Lilly, Novartis, Pfizer, Sun, and UCB, Consultant for: AbbVie, Amgen, Bristol Myers Squibb, Celgene, Janssen, Lilly, Novartis, Pfizer, Sun, and UCB, Speakers bureau: AbbVie, Amgen, Bristol Myers Squibb, Celgene, Genentech, Janssen, Novartis, Pfizer, and UCB, N. Accortt Shareholder of: Amgen Inc., Employee of: Amgen Inc., S. Rebello Employee of: Corrona LLC, C. Etzel Consultant for: Merck, Employee of: Corrona LLC, R. Harrison Employee of: Corrona LLC, G. Aras Shareholder of: Amgen Inc., Employee of: Amgen Inc., M. Gharaibeh Shareholder of: Amgen Inc., Employee of: Amgen Inc., J. Greenberg Shareholder of: Corrona LLC, Consultant for: Genentech, Janssen, Novartis, Pfizer, and Eli Lilly, Employee of: Corrona LLC, D. Collier Shareholder of: Amgen Inc., Employee of: Amgen Inc.